Perancangan Sistem Simulasi Open Close Recloser - ANGGA W., Abi Daud ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Grounding short circuit fault Is fault that most often occurs in the power system, including in duri field PT.CPI 13.8 kV and 0.48 kV , where the simulation studied . Recloser is one of grounding short circuit protection tools. With Recloser simulation system Open close using EMTP 3.1 software in ATP Draw as well as the data acquisition simulation system can give clear description of short circuit fenomenon. The methods that used in identifying transient conditions change detection methods are the current and voltage at the open and close system mechanical recloser due to grounding line system that makes short circuit happened. Based on test results, ATP Draw were capable to displaying or storing data in short circuit current and voltage graphs. The test results indicate that a earth short circuit at the 4 th area point was simulated at a distance of 1 km to 8 km from the recloser, and identified with the increase in the maximum current was reached to 88 331 A , the maximum short circuit voltage was reached to 657.19 V, and 238.78 V for a maximum voltage drop in phase. By doing this simulation, it is known that the distance of the recloser and the number of load lost due to short circuit earthing greatly affect to the magnitude of current and voltage system. At the current changes closer short circuit conditions to the recloser, the higher short ciruit current flow to the sistem, while the voltage changes, voltage drop will reach the lowest point is at 238.78 V, but the voltage transient will reach the maximum voltage at 657.19 V. Recloser protection system settings using kyle rules do not provide a great effect on the changes in current and voltage value when the short circuit happen, instead only affects in the duration of recloser reaction to faults, so the period of faults that system have to sustained was according to the Kyle setting time and delay recloser time . Fault system simulation in recloser performance was very useful in improving the understanding of the faults and its effects to the system